Ekologik ong va fizika: maktab o‘quvchilarida ilmiy tafakkur va mas’uliyatli munosabatni shakllantirish (SCIENCE and SOCIETY, 2025)
This article examines the role of physics in shaping a sustainable ecological worldview in schoolchildren and analyzes conservation laws, basic physical principles such as thermodynamics and mechanics, as well as their relationship with ecological processes and technological progress. Also, in the school physics course, methods of integrating environmental education through laboratory experiments and project-based learning are discussed.